Pectobacterium brasiliense 1692 Chemotactic Responses and the Role of Methyl-Accepting Chemotactic Proteins in Ecological Fitness - Tanui, Collins Kipngetich; Shyntum, Divine Yutefar; Sedibane, Precious K.; Bellieny-Rabelo, Daniel; Moleleki, Lucy N. (Frontiers in Plant Science, 2021)
To adapt to changing environmental niches, bacteria require taxis, a movement towards or away from a stimulus (ligand). Chemotaxis has been studied in some members of the Soft Rot Pectobacteriaceae (SRP), particularly members of the genus Dickeya. On the contrary, there are fewer studies on this topic for the other genus in the SRP group, namely Pectobacterium. This study evaluated chemotactic responses in Pectobacterium brasiliense (Pb 1692) to various ligands. A total of 34 methyl-accepting chemotactic proteins (MCPs) were identified in the Pb 1692 genome and the domain architectures of these MCPs were determined. Four Pb 1692 MCPs previously shown to be differentially expressed during potato tuber infection were selected for further functional characterization. Towards this end, Pb 1692 mutant strains each lacking either AED-0001492, AED-0003671, AED-0000304, or AED-0000744 were generated. Two of these mutants (AED-0001492 and AED-0003671), were attenuated in their ability to grow and respond to citrate and are thus referred to as MCPcit2 and MCPcit1, respectively, while the other two, AED-0000304 (MCPxyl) and AED-0000744 (MCPasp), were affected in their ability to respond to xylose and aspartate, respectively. Trans-complementation of the mutant strains restored swimming motility in the presence of respective ligands. The four MCP mutants were not affected in virulence but were significantly attenuated in their ability to attach to potato leaves suggesting that ecological fitness is an important contribution of these MCPs towards Pb 1692 biology.